2013
DOI: 10.1089/neu.2012.2399
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Mild Traumatic Brain Injury: Mechanisms of Cerebral Vulnerability

Abstract: Among the 3.5 million annual new head injury cases is a subpopulation of children and young adults who experience repeated traumatic brain injury (TBI). The duration of vulnerability after a single TBI remains unknown, and biomarkers have yet to be determined. Decreases in glucose metabolism (cerebral metabolic rate of glucose [CMRglc]) are consistently observed after experimental and human TBI. In the current study, it is hypothesized that the duration of vulnerability is related to the duration of decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
218
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 293 publications
(238 citation statements)
references
References 81 publications
11
218
1
1
Order By: Relevance
“…254 Finally, pediatric populations exhibit different responses to adults experiencing a similar head trauma, 255 and limited studies have been conducted assessing younger populations. 235,236,256,257 Conclusions Long-term cognitive impairments following CNS injury and in neurodegenerative diseases have been associated with prolonged oxidative stress conditions 131,258 and impaired signal conduction along dysmyelinated axons. 259 Further, persisting behavioral deficits after TBI have been associated with progressive activation of astrocytes 260 and microglia.…”
Section: Barriers To Clinical Translationmentioning
confidence: 99%
“…254 Finally, pediatric populations exhibit different responses to adults experiencing a similar head trauma, 255 and limited studies have been conducted assessing younger populations. 235,236,256,257 Conclusions Long-term cognitive impairments following CNS injury and in neurodegenerative diseases have been associated with prolonged oxidative stress conditions 131,258 and impaired signal conduction along dysmyelinated axons. 259 Further, persisting behavioral deficits after TBI have been associated with progressive activation of astrocytes 260 and microglia.…”
Section: Barriers To Clinical Translationmentioning
confidence: 99%
“…38 Similarly, Prins and colleagues demonstrated that two injuries separated by 24 h were associated with a greater and more persistent decrease in cerebral metabolism than either a single injury or two injuries separated by three days in rats. 39 The evolution of secondary injury also likely depends upon the brain injury mechanism with different injury models yielding varying time dependencies. Duhaime and colleagues used a porcine controlled cortical impact model and although they also found peak lesion volumes in five-day-old piglets at one day post-injury, fourweek-old piglets had peak lesion volumes at seven days postinjury.…”
Section: Figmentioning
confidence: 99%
“…9 This metabolic disruption lasts about a week, mirroring the timeline of clinical symptom recovery. 10,11 In animal models, researchers 12 have demonstrated that a second concussion during this period of brain vulnerability creates greater metabolic and cognitive impairment for a longer time. Similar findings of vulnerability and impaired recovery have also been shown in male athletes.…”
mentioning
confidence: 99%
“…13 Removing injured athletes from participation close to the time of injury reduces the risk of secondary injury when they are vulnerable to the cumulative effect of concussions. [12][13][14] However, given underreporting, 5,7 transient symptoms, 15 delayed onset of symptoms, 16 and the few concussions occurring with loss of consciousness, concussions are often difficult to detect and diagnose. [17][18][19] Therefore, objective and quantitative diagnostic tools that are more sensitive and specific to concussive injury are needed.…”
mentioning
confidence: 99%